Transferring research from a university to the United Kingdom National Health Service: the implications for impact - Helen Payne (BMC, 2017)
Abstract The aim of this article is to inform readers of the author's reflections on the experience of transferring university-based research into the commercial sector, and of the processes and strategies employed when preparing for impact in so doing. Concepts for the transfer are illustrated by the author's reflection on aspects that arose during the birthing and subsequent start-up of a university spin-off, Pathways2Wellbeing, a form of reflection-on-action. This is the vehicle for the adaption required to transfer research into the delivery of a specialised clinic in the United Kingdom National Health Service for people with medically unexplained, persistent, bodily symptoms such as fibromyalgia, chronic fatigue and chronic pain. It is hoped that the article will provide readers with an insight into how knowledge transfer can take place through engagement with stakeholders to create an exchange of knowledges to result in impact on health service policy for service users, despite the challenges, and the enablers that facilitated this process. The reflections on the process of knowledge transfer and the implications for impact are underpinned by relevant theory.